Pembentukan Karakter Peserta Didik di Sekolah Dasar Melalui Pembelajaran Kepramukaan - Yola Adelya Azhari; Nabilah Assyifa Lubis; Nur Hana; Auliya Sakinah; Fajar Siddik Siregar (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this study is to describe the process of developing students' character through Scouting education and to find out the elements that support and hinder Scouting activities in elementary schools. Students, teachers, and community members are the topics of this qualitative research. Methods to obtain data with research, observation, and documentation. The main tool used is the use of instruments for data collection of observation, interviews, and documentation. The results emphasize how important scouting activities are in helping students develop independent, mutual cooperation, nationalist, religious, and ethical traits. Daily scout lessons are used to implement these activities; scout activities, marching activities, and educational resources are used in the Dasadarma and SKU by using five different teaching approaches, namely punishment or sanctions, exemplary, habituation, lecture, and habituation.